Media Coverage of Climate Change and Sustainable Product Consumption: Evidence from the Hybrid Vehicle Market - Chen, Yubo; Ghosh, Mrinal; Liu, Yong; Zhao, Liang (Journal of Marketing Research, 2019)
As sustainable consumption becomes increasingly important, firms must better understand the drivers behind the consumption of these products. This article examines the effects of mass media in the context of the U.S. hybrid vehicle market. Drawing on monthly sales data, the authors provide evidence that the general coverage of climate change or global warming by major media outlets exerts an overall positive impact on the sales of hybrid vehicles. This impact mainly comes from the media reports that assert that climate change is occurring. In contrast, media coverage that either denies climate change or holds a neutral stance on the issue has little impact. The authors provide preliminary evidence that a social norm advocating for environmentally friendly consumption plays an important role in how media coverage affects consumer purchase. They provide implications for theory and practice and call for future research that examines the causal impact of media in general on consumer decisions, especially in domains that are crucial for the society.